Identification in milk of a serum amyloid A peptide chemoattractant for B lymphoblasts (2009)
ABSTRACT: Background: Normal mammary gland contains an extravascular population of B lymphoblasts, precursors of the immunoglobulin plasma cells that play a key role in the passive protection of neonates by secreting immunoglobulins to colostrum and milk. We investigated the presence of chemoattractants in the milk by analysing the chemoattractant activity of various fractions of this secretion. Milk chemoattractants are potentially involved in the recruitment of lymphocytes from the maternal bloodstream in lactating mammary glands. Results: The dilution-related lymphoid cell chemoattraction of whey was associated with a < 10 kDa ultrafiltrate. Active fractions were purified by reverse-phase high performance liquid chromatography. Two peptides of 2.7 kDa (DMREANYKNSDKYFHARGNYDAA) and 1 kDa (RPPGLPDKY) were identified as fragments of the SAA protein family, tentatively identified as SAA2. Only the 2.7 kDa synthetic peptide displayed chemotactic activity, at two different optimal concentrations. At the lower concentration (3.7 nM), it attracted B-cell lymphoblasts, whereas at the higher (3.7 μM), it attracted B lymphocytes. Then, the SAA mRNA expression was analysed and we observed more SAA transcripts during lactation than gestation. Conclusion: These data are consistent with the SAA23–45 fragment being involved in preplasma B cell recruitment to the mammary gland and resultant benefit to the neonate.